2023
DOI: 10.1021/acsami.3c06150
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Microfluidic-Based Low-Cost and High-Speed Microsphere Array Direct Writing Technology and Its Applications

Abstract: Microsphere arrays have significant applications and broad development prospects in various fields and disciplines. The simple, efficient, low-cost, automatic, and controllable preparation of microsphere arrays in multiple dimensions and morphologies is still a significant challenge. Here, a novel microsphere array direct writing technology was developed using a lowcost portable droplet microfluidic device and a high-precision XY movable platform. The proposed technology provided a powerful platform for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recent research in this direction has lead to the development of off-the-shelf device designs that can produce complex emulsions in the desired pattern and in relatively higher volumes. Guo et al (2023) has shown that complex emulsions can be 3D printed in desired patterns [ 74 ]. Furthermore, the authors have shown the device’s versatility in achieving spheroids within complex emulsions [ 116 ].…”
Section: Challenges and Possibilities In Designing Complex Emulsions-...mentioning
confidence: 99%
“…Recent research in this direction has lead to the development of off-the-shelf device designs that can produce complex emulsions in the desired pattern and in relatively higher volumes. Guo et al (2023) has shown that complex emulsions can be 3D printed in desired patterns [ 74 ]. Furthermore, the authors have shown the device’s versatility in achieving spheroids within complex emulsions [ 116 ].…”
Section: Challenges and Possibilities In Designing Complex Emulsions-...mentioning
confidence: 99%